Attitude wanna make something of it? : the secret of stand-up comedy - Allen, Tony (Gothic Image Publications, 2002)
This guide to comedy is written in a humorous style, and should appeal to readers interested in the history of stand-up, would-be comedians and wannabe messiahs, as well as those who just like a laugh
Keywords: Stand-Up Comedy; Stand-up comedy; Bibliografie